A festschrift in honor of Vernon W. Hughes : Yale University, 13 April 1991 - Zeller, Michael E. (World Scientific, 1992)
The contents of this book are derived from a celebration of the 70th birthday of Vernon W Hughes. Professor Hughes' career has touched on several areas in modern physics ranging from precision measurements of the fundamental properties of atoms to measurements of spin structure functions of the proton via deep inelastic muon scattering at the world's highest energy fixed target machines.